Making the Case for Addressing Health Disparities: What Drives Providers and Payers? - Margaret Johnson; Heather McPheron; Rachel Dolin; Julia Doherty; Lisa Green (Mary Ann Liebert, 2018)
Purpose: The creation of the Centers for Medicare & Medicaid Services Office of Minority Health placed increased emphasis on federal efforts to address health disparities. Although the literature establishes a social justice case for addressing health disparities, there is limited evidence of this case being sufficient for businesses to invest in such initiatives. The purpose of this study was to better understand the ?business case? behind an organization's investment in health disparity reduction work. Methods: We conducted six case studies (44 on-site interviews) with diverse private-sector provider and payer organizations. Results: While providers and payers cited business rationales for initiating disparity-focused efforts, their motivations differed. Conclusion: As federal entities address health disparities, and payment models shift from volume to value, engaging private stakeholders with the leverage to move the health disparities needle is of principal importance.